Learning From Science News via Interactive and Animated Data Visualizations: An Investigation Combining Eye Tracking, Online Survey, and Cued Retrospective Reporting. Issue 6 (December 2020) - Greussing, Esther; Kessler, Sabrina Heike; Boomgaarden, Hajo G.
Relying on a multimethod approach with eye tracking, cued retrospective reporting, and a memory test, this experimental study ( N = 45) shows how individuals engage with static, interactive, and interactive-animated data visualizations embedded in online science news. The results suggest that interactivity and animation engage participants most strongly: The second part of the news article is fixated the longest by participants exposed to the interactive-animated visualization, which translates into higher learning outcomes. However, the dynamic process of news reception requires a nuanced understanding of how users attend to visual and textual parts of a message to make informed statements about their effectiveness.